2017
DOI: 10.3390/antibiotics7010003
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a System for Testing Replication Inhibition of the Vibrio cholerae Secondary Chromosome in Escherichia coli

Abstract: Regulators of DNA replication in bacteria are an attractive target for new antibiotics, as not only is replication essential for cell viability, but its underlying mechanisms also differ from those operating in eukaryotes. The genetic information of most bacteria is encoded on a single chromosome, but about 10% of species carry a split genome spanning multiple chromosomes. The best studied bacterium in this context is the human pathogen Vibrio cholerae, with a primary chromosome (Chr1) of 3 M bps, and a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…cholerae ori2 , it was shown that the copy number increases in an E . coli strain carrying a copy of the crtS site; this did not occur in a strain lacking crtS [ 27 , 33 ]. As readout for the replicon copy number, we measured how well each strain tolerated increased amounts of antibiotic ( Fig 5 , see Method section for details, [ 34 ]).…”
Section: Resultsmentioning
confidence: 99%
“…cholerae ori2 , it was shown that the copy number increases in an E . coli strain carrying a copy of the crtS site; this did not occur in a strain lacking crtS [ 27 , 33 ]. As readout for the replicon copy number, we measured how well each strain tolerated increased amounts of antibiotic ( Fig 5 , see Method section for details, [ 34 ]).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum origin of replication contains the rctB encoding gene and six repeated 12-mers (iterons) onto which RctB binds to promote replication initiation with the unwinding of a contiguous AT-rich sequence ( 13 ). It also contains putative IHF and DnaA binding sites, the latter being required for replication at ori2 ( 14 , 15 ). The ori2 regulatory region contains a transcribed but non-translated ORF ( rctA) and two types of RctB binding sites: five regulatory iterons and two 39-mer motifs, one of which is found in rctA ( 16 ) .…”
Section: Introductionmentioning
confidence: 99%
“…This phenotype was shown to be directly linked to improper regulation/activation of Chr2 replication ( 33 ). The presence of a crtS- containing plasmid in E. coli enhances the replication of an ori2 -driven plasmid ( 15 , 22 ). Serial deletions of a DNA fragment containing crtS in a plasmid showed that the replication-enhancing activity of an ori2 -driven plasmid in E. coli could be narrowed down to a 70-mer site (chrI-9) ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that there is a high degree of variance in oriC structure between taxonomic classes (7,43), we limited the scope of γBOriS to Gammaproteobacteria. Furthermore, as most secondary chromosomes do not rely on the initiator protein DnaA for replication initiation (48,49), and as they are rather rare in bacterial cells (3), we also excluded these from the scope of the tool and focused only on primary chromosomes. Using different training datasets, the general approach of γBOriS can easily be adapted for other groups of organisms.…”
Section: Discussionmentioning
confidence: 99%